Provision Of Health Education For Pre Hospital Handling Of Traffic Accident Victims On Knowledge And The Attitude Of The Community In Tinalan Village Kediri City - Yohanis Umbu Robaka; Yuli Peristiowati; Heri Saputro (Journal of Hospital Management and Services, 2020)
The high number of deaths from traffic accidents is still one of the problems encountered in the State of Indonesia, and one of the factors that affect the high number of casualties is due to the slow handling death were waged against victims accidents traffic. The aim of research for the effect of education healt h pre- hospital on the victims of traffic accidents on knowledge and attitudes in the Village Tinalan Kediri. Research design pre-experimental approach of one-group pre-post test. Respondents were drawn using purposive sampling technique. Population The whole community of road users in Kelurahan Tinalan Kediri. Sample of 41 respondents. Independent Varabel of helath education, dependent variable of knowledge and attitude. Results were analyzed using the Wilcoxon statistical test. The results showed the majority of respondents have less knowledge before health education as many as 30 respondents (73.2%), almost all respondents had an attitude negative before health education as many as 34 respondents (82.9%), the majority of respondents have a good p se What Knowledge categories have health education as many as 23 respondents (56.1%), almost all respondents had an attitude with positive categories had been given health education se as many as 35 respondents (85.4%) of the total 41 respondents. Results of analysis addressing p-value = 0.000 <α 0.05, so the H1 accepted which means there is the effect of education health pre- hospital on the victims of traffic accidents on knowledge and attitudes in the Village Tinalan Kediri. Increased knowledge and attitude change towards the positive Tinalan Village community in handling traffic accident victims influenced by the information provided by the researchers through health education on handling the victims of traffic accidents so that people are aware of the importance of first aid to the victims of accidents.